METODE HEAT TREATMENT PADA PENGUJIAN KEKERASAN LOGAM ALUMINIUM DENGAN VARIASI MEDIA PENDINGIN - Rani, Sefrilita Risqi Adikaning; Nurrahmi, Sitti (SAINFIS: Jurnal Sains Fisika, 2021)
Research has been carried out on the effect of cooling media on the hardness of aluminum metal using the heat treatment method. Heat treatment is a method that can be used to change the mechanical properties of a material. The purpose of this experiment is to determine the hardness value of a material with the quenching method and to determine the effect of fluid viscosity on the hardness value of a material. In this case the material is Aluminum Metal. The principle used in this experiment is quenching, which is heating until it reaches a critical temperature for aluminum metal and cooled with a cooling medium. Based on the experiments that have been carried out, it can be concluded that the viscosity value obtained from the material after quenching with water cooling media is 44.5 HV, while the metal cooled using oil media has a hardness of 35.5 HV. The viscosity value of the media greatly affects the hardness value of Aluminum metal, the greater the viscosity value of a cooling medium, the smaller the viscosity value and the smaller the viscosity value of the cooling medium, the greater the hardness value of aluminum metal.